PREPARING FUTURE TEACHER-EDUCATORS FOR DESIGNING A DEVELOPMENTAL OBJECT-SPATIAL ENVIRONMENT IN PRESCHOOL INSTITUTIONS - Raziya Karimova Eleupanovna; Anar Aymoldanovna Alimbekova; Yücel Gelişli (Research Retrieval and Academic Letters, 2025)
The article examines the theoretical and methodological foundations of preparing future preschool educators and teachers to design a subject-developing environment in kindergarten. Based on modern interpretations of the concept of "educational environment," the authors present a series of recommendations for future preschool educators on organizing the educational process with preschool children within the framework of a subject-developing environment. Additionally, by analyzing leading domestic research on the subject-developing environment, the authors explore the requirements of core regulatory documents and the content components of the "Model Curriculum for Preschool Education and Training." The authors conceptualize the design of a subject-developing environment as a set of fundamental principles: content saturation, transformability, accessibility, multifunctionality, and safety. Currently, the "zoning" of group spaces in kindergartens is considered an effective and modern approach. Designing a subject-developing environment in kindergarten groups requires future educators to possess personal and professional readiness for pedagogical practice, as it involves not only knowledge and skills in creating and transforming such environments but also flexibility in adapting to situational conditions directly tied to the individual characteristics of children. The proposed recommendations can be integrated into the preparation of future educators and teachers within the framework of lifelong education